Mobile Stones: The Uses and Meanings of Earth Science Teaching Specimens - Chalk, Hannah-Lee (Material Culture Review, 2012)
The origins of university earth science teaching specimens are diverse; while some objects are collected specifically for teaching purposes and therefore travel directly from the field into a teaching collection, for others, the journey is less straightforward. Indeed, a considerable amount of the material that is used for teaching in the earth sciences has in fact been recycled from other (mostly research-related) activities, purchased from wholesalers, or borrowed from museum collections, and was therefore not originally intended to function in this context. But how are such objects made to work as teaching specimens? What happens to their previous meanings? Do they function any diﬀerently from those objects that have been collected specifically for teaching purposes? In addressing these questions, this paper reveals that, far from being fixed, static, and stable—far from being “set in stone”—these objects are polysemic, flexible, and mobile.